Blending Personal Health, Family Matters and Personal Time Management for the Best Work-life Balance - Saad, Mazni; Jaafar, Aishah Nawwarah; Ong, Mohd Hanafi Azman; Yulinda, Eni; Kumarasamy, Mokana Muthu; Mahmod, Razmah (Society for Science and Education, 2024)
This paper aims to develop a theoretical perspective to better understand hospitality workers’ behaviours in blending family life and work for the best worklife balance. The perspective is guided by social exchange theory. It examines 320 hospitality workers’ behaviour that has high levels of positive valence to be most influential for their work-life balance due to profitable relationships. We describe these theoretical principles and sub-principles concerning hospitality workers to build a research agenda to encourage future research. A response rate of 28% from food and beverage companies participated in the online survey via the web-based questionnaire design. The results indicate that family matters, time management, and personal health bring 60% of predictions for F&B workers’ work-life balance. Three predictors were positive and significantly affected the work-life balance, with personal health being the biggest influence, followed by family matters, and time management. Implications, limitations, and recommendations are also discussed at the end of this paper.